STUDI KEDUDUKAN DA N KEWENANGA N DESA DINAS DA N DESA PAKRAMAN DI PROVINSI BALI (Desa Ekasari Kecamatan Melaya dan Desa Asah Duren Kecamatan Pakutatan Kabupaten Jembrana Bali) - Siti Nur Solechah (Jurnal Politica, 2012)
This essay made based on the research on the status and power of the so-called Official Village (Desa Dinas) and Traditional Villages (Desa Pakraman). The research uses a qualitative method whose data gathering is conducted by making observations and indepth interview. Its findings shows that each type of the villages has its own authority and regulations, in which there are no conflict of interest. There is no worry, therefore, that they will weaken each other.